Risk and factors related to the development of lesions due to xerosis in hospitalized elderly people - de Oliveira Cruz, Ronny Anderson; Braz Evangelista, Carla; Alves da Silva, Mirian; Damaso de Araújo, Cleide Rejane; dos Santos Oliveira, Jacira; Lopes Costa, Marta Miriam (Investigación y Educación en Enfermería, 2025)
Objective. To analyze the risk and factors related to the development of skin lesions due to xerosis in hospitalized elderly people. Methods. This was a descriptive and cross-sectional study with 455 elderly people hospitalized in Paraíba (Brazil). The Risk Assessment Scale for the Development of Lesions Associated with Xerosis Cutis in Elderly People (ERLAX-53) developed in Brazil by Cruz in 2023 was used. Results. The sample consisted of 272 (59.8%) elderly people from the medical clinic and 183 (40.2%) from the ICU, most of whom were females (54.5%). There were high frequencies of the variables “immobility” (58.9%), “friction and shear” (87.7%), “presence of comorbidities” (99.3%) and “predominance of dry skin” (79.8%). The correlation was positive and moderate for “mobility”, “level of consciousness”, “tactile sensitivity”, “temperature” and “phototype”. As for the risk of lesions associated with xerosis, 337 (74.1%) were at medium risk and 101 (22.2%) at high risk. Conclusion. 96.3% of the elderly people with xerosis cutis who participate in the study were at medium to high risk of developing additional skin lesions, which is why nursing must implement preventive and treatment strategies to care for these people.